Final adult height of patients with childhood-onset systemic lupus erythematosus: a cross sectional analysis - Merav Heshin-Bekenstein; Liat Perl; Aimee O. Hersh; Emily von Scheven; Ed Yelin; Laura Trupin; Jinoos Yazdany; Erica F. Lawson (BMC, 2018)
Abstract Background To compare final height to mid-parental target height among adults with childhood-onset systemic lupus erythematosus (cSLE) versus adult-onset SLE (aSLE), and to evaluate the impact of age at SLE onset on final height. Methods Data derived from the Lupus Outcomes Study, a longitudinal cohort of adults with SLE, was used for this cross-sectional analysis (N = 728). Participants aged 18-63 years with complete height data were included (N = 566) and were classified as cSLE if age at diagnosis was < 18 years (N = 72). The Tanner formula was used to calculate mid-parental target height. Multivariate linear regression was used to determine mean difference between final height and target height. Multivariate logistic regression was used to compare odds of substantially reduced final height, defined as > 2 SD below target height. Separate analyses were conducted for females and males to account for differences in timing of the pubertal growth spurt for each sex. Results Participants with cSLE were, on average, 2.4 cm shorter than their target height (95% CI -4, − 0.7). The adjusted odds ratio (OR) for substantially reduced final height was 3.9 (95% CI + 2.0, + 7.2, p < 0.001) as compared to participants with aSLE. Females diagnosed between 11 and 13 years were at greatest risk for substantially reduced final height, with adjusted OR of 11.2 (95% CI + 3.4, + 36.3) as compared to participants with aSLE (p < 0.001). Conclusions cSLE is associated with shorter-than-expected final height. Onset of SLE in the pubertal period, near the time of maximum linear growth, may have a particularly significant impact on final height.